How Mandarin–English bilinguals interpret qián/forward: impact of language proficiencies on retrieval of temporal concepts - Yang, Tengji; Yang, Ying (Frontiers in Psychology, 2024)
Mandarin qián and English forward are semantically equivalent in the domain of Space, but could be semantically opposite in the domain of Time. In other words, equivalent spatial lexical items could convey opposite temporal concepts. What temporal concepts conveyed by qián and forward would be retrieved by Mandarin-English (M-E) bilinguals with different language proficiencies? Drawing a sample from college students in Mainland China, this study examines how L1 and L2 proficiencies would affect M-E bilinguals' retrieval of temporal concepts by examining their interpretation of the Mandarin temporal metaphor of qián and the English temporal metaphors of forward. The results show that L1 temporal concepts would be retrieved more frequently than L2 temporal concepts regardless of the testing languages, that L1 and L2 proficiencies were not predictors for the way of interpretation, and that the higher L2 proficiency group could retrieve temporal concepts in line with the testing languages with higher accuracy than the lower L2 proficiency group. The findings suggest that bilinguals with higher L2 proficiency may be able to represent temporal concepts with language tags, or may have an attentional and/or inhibitory control advantage.